Aydın İli Efeler İlçesi'nin 1993-2021 Yılları Arasında Arazi Örtüsü Değişimlerinin Coğrafi Analizi - Keloğlu, Emre; Karabacak, Kerime (Fırat University, 2025)
Arazi örtüsü değişimi, bitki örtüsü, toprak örtüsü ve yerleşim örtüsü gibi farklı arazi örtülerinin fiziksel özelliklerindeki değişiklikleri ifade etmekte olup, bu değişimler genellikle kentleşme, yeni tarım alanlarının açılması ve ormanların tahribi gibi antropojenik faaliyetler ve doğal süreçler sonucunda gerçekleşmektedir. Sosyoekonomik faaliyetler sonucunda kontrolsüz şekilde gerçekleşen arazi örtüsü değişimleri, yerel, bölgesel ve küresel ölçekte olumsuz çevresel etkiler yaratmaktadır. Bu çalışmada, Aydın İli Efeler İlçesi'nin 1993 ve 2021 yıllarına ait arazi örtüsü değişimleri, Coğrafi Bilgi Sistemleri (CBS) ve Uzaktan Algılama (UA) teknikleri kullanılarak analiz edilmiş ve bu değişimlerin boyutları ile nedenleri coğrafi perspektif ile incelenmiştir. Belirlenen altı arazi örtüsü sınıfı arasında yapılan karşılaştırmalar sonucunda; yerleşim alanlarının %85,2 ve diğer alanların %19 oranında arttığı tespit edilmiştir. Buna karşın, tarım alanları %7, ormanlar %4, mera alanları %30,1 ve zeytinlikler %2 oranında azalmıştır. Efeler ilçesindeki arazi örtüsü değişimlerinin ana nedenleri ise kentleşme, yeni tarım alanlarının açılması, ormanların tahrip edilmesi ve maden sahalarının oluşturulması olarak belirlenmiştir. Bu süreçte, verimli tarım topraklarının kentleşme nedeniyle kaybedildiği ve ormanların ise yerleşim ve tarım alanlarının baskısı altında olduğu tespit edilmiştir.

Land cover change refers to alterations in the physical characteristics of various land covers such as vegetation, soil, and settlement patterns. These changes typically arise from anthropogenic activities like urbanization, expansion of agricultural areas, and deforestation, as well as natural processes. Uncontrolled land cover changes due to socioeconomic activities lead to adverse environmental impacts at local, regional, and global scales. This study examines the land cover changes in Efeler District of Aydın Province between 1993 and 2021 using Geographic Information Systems (GIS) and Remote Sensing (RS) techniques to analyze their dimensions and underlying causes from a geographical perspective. Comparisons among six identified land cover classes reveal that urban areas increased by 85.2% and other areas by 19%. In contrast, agricultural lands decreased by 7%, forests by 4%, grasslands by 30.1%, and olive groves by 2%. The primary drivers of land cover changes in Efeler District are identified as urbanization, expansion of agricultural areas, deforestation, and establishment of mining areas. During this process, it is noted that productive agricultural lands are lost due to urbanization, while forests are pressured by urban and agricultural Land cover change refers to alterations in the physical characteristics of various land covers such as vegetation, soil, and settlement patterns. These changes typically arise from anthropogenic activities like urbanization, expansion of agricultural areas, and deforestation, as well as natural processes. Uncontrolled land cover changes due to socioeconomic activities lead to adverse environmental impacts at local, regional, and global scales. This study examines the land cover changes in Efeler District of Aydın Province between 1993 and 2021 using Geographic Information Systems (GIS) and Remote Sensing (RS) techniques to analyze their dimensions and underlying causes from a geographical perspective. Comparisons among six identified land cover classes reveal that urban areas increased by 85.2% and other areas by 19%. In contrast, agricultural lands decreased by 7%, forests by 4%, grasslands by 30.1%, and olive groves by 2%. The primary drivers of land cover changes in Efeler District are identified as urbanization, expansion of agricultural areas, deforestation, and establishment of mining areas. During this process, it is noted that productive agricultural lands are lost due to urbanization, while forests are pressured by urban and agricultural activities.
Geographical Analysis of Land Cover Change Between 1993-2021 in Efeler District of Aydın Province
Keywords: Environmental Assessment and Monitoring; Çevresel Değerlendirme ve İzleme